The Implementation of International Standardization Organization (ISO) 9001 in Educational Institutions - Aquirera, Sisi; Radiana, Usman (Jurnal Manajemen Pendidikan, 2025)
Background Related to business, including introducing products and services to the world community. Quality refers to a dynamic condition related to products, services, individuals, processes, and environments that meet or exceed established expectations. The main focus is on continuous improvement to create products and services that have competitive quality at the global level. Purpose The purpose of this study is to explore and understand the concept of ISO (International Organization for Standardization), including its history, types, and significance, particularly in the context of educational institutions. Design/method/approach This research uses a qualitative descriptive approach, focusing on literature study as the primary method. The data were collected through the review and analysis of various sources such as scientific journals, books, and credible internet articles related to ISO standards, particularly ISO 9001, and their implementation in educational institutions. Results The results of this study indicate that ISO, particularly ISO 9001, plays a vital role in enhancing the quality management systems within educational institutions. Schools that implement ISO standards show improved organizational structure, clearer documentation processes, and increased stakeholder satisfaction. The study also finds that ISO certification encourages continuous improvement and helps schools gain greater credibility and competitiveness on both national and global levels. Contribution/value This research contributes to the understanding of how ISO 9001 certification impacts the quality management systems in educational institutions. The study provides valuable insights into how schools can align their internal quality assurance systems with international standards, thereby enhancing educational service delivery.